"Growing foods from home": food production, migrants and the changing cultural landscapes of gardens and allotments. (2nd October 2016) - Gerodetti, Natalia; Foster, Sally
Abstract: The study arises out of research that explored how migrant identities are constructed in relation to food practices in a Northern city. Using narrative accounts and participant observation collected through a small-scale qualitative study, we examine how, in using gardens and allotments to "grow foods from home" alongside locally established fruit and vegetables, a landscape approach allows us to see how migrant gardeners are reshaping existing cultural landscapes and constructing places of belonging. Whilst these landscapes can be viewed visually as representations of both traditional and hybrid practices, the study draws on non-representational theories in landscape to explore emotions, embodiment, performance and practice. Such an approach uncovers some of the differences in the meaning of food production for diasporic and non-diasporic migrant gardeners.